The Role Of Digital Technologies In Tourism: AI, Big Data, IoT - Khusanova, Shodiya (TLEP – International Journal of Multidiscipline, 2026)
This article highlights the digital technologies that play an important role in the tourism sector, namely artificial intelligence, the Internet of Things, and big data. These technologies also play an important role in services such as further enriching the quality of tourism services, increasing management efficiency, and identifying customer needs.